Determinan Repurchase Intention Brand Wardah di TikTok: Peran Brand Love sebagai Moderasi - Novi Rahma Juwanti; Heni Susilowati (Universitas Nusantara PGRI Kediri, 2026)
This research intends to examine the moderating role of brand love in the effects of influencer marketing and brand image on the repurchase intention for Wardah products on TikTok. A quantitative approach and causal design were adopted, with the data gathered from an online survey of 100 TikTok users who had been exposed to Wardah content. PLS-SEM was utilized to analyze and hypothesis testing. The main conclusions of this study demonstrate that influencer marketing and brand love positively and significantly affect the intention to repurchase, whereas brand image provides a negative outcome. Furthermore, brand love was found to strengthen the association amongst influencer marketing and the repurchase intention for Wardah products. However, brand love does not moderate the correlation amongst brand image and the repurchase intention. Wardah products. These results confirm that optimizing the role of influencer marketing and fostering emotional connections with customers is more critical than brand image perceptions in driving repurchase intent.